PEMANFAATAN ALAT SURVEI GPS GEODETIK CHCNAV i50 TERHADAP AKURASI DATA JARINGAN PIPA PAM JAYA - Fakhruddin, Faris; Prabowo, Andy (Jurnal Bakti Masyarakat Indonesia, 2024)
One of the activities of the PAM JAYA GIS (Geographic Information System) team is to conduct surveys and measurements in the West and East regions of PAM JAYA's service area using the CHCNAV i50 Geodetic GPS to produce accurate and precise pipe network position data. Regional Public Company (Perumda) Air Minum Jaya, commonly known as PAM JAYA, is a company engaged in the field of clean water supply services. This project is undertaken considering the numerous layered pipe networks owned by PAM JAYA buried under concrete/asphalt, thus facilitating PAM JAYA's partner vendors in locating points or coordinates of buried pipe networks in the streets of the DKI Jakarta and Thousand Islands areas. PAM JAYA chose the CHCNAV i50 Geodetic GPS because it has a receiver accuracy of 20 cm radius, making it suitable for detecting the dimensions of PAM JAYA's accessories measuring 40 x 60. This research is a quantitative type utilizing secondary data consisting of plotting results obtained from ABD (as-built drawing) by the PAM JAYA construction team and the results of Geodetic GPS surveys. The technique used to analyze the data is to compare the calculation results from the Euclidean Distance method, which applies the Pythagorean concept, to the actual results from the use of CHCNAV i50 Geodetic GPS. The comparison results indicate a discrepancy between the plotting results from the Pythagorean calculations and the GPS survey results, with a displacement radius of less than 20 meters ABSTRAK Salah satu kegiatan tim GIS (Geographic Information System) PAM JAYA yaitu melakukan survei dan pengukuran di Wilayah Barat dan Timur. Perusahaan Umum Daerah (Perumda) Air Minum Jaya yang biasa disebut PAM JAYA adalah perusahaan yang bergerak dibidang pelayanan penyediaan air bersih.  Pelayanan PAM JAYA menggunakan GPS Geodetik CHCNAV i50 untuk menghasilkan data posisi jaringan pipa yang akurat dan tepat. Proyek ini dilaksanakan mengingat banyaknya jaringan pipa berlapis milik PAM JAYA yang tertimbun beton/aspal, sehingga memudahkan vendor mitra PAM JAYA dalam mencari titik atau koordinat jaringan pipa yang tertanam di jalan-jalan area DKI Jakarta dan Kepulauan Seribu. PAM JAYA memilih GPS Geodetik CHCNAV i50 karena memiliki ketelitian receiver radius 20 cm, sehingga cocok untuk mendeteksi ukuran  panjang dan lebar aksesoris PAM JAYA 40 x 60. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan data sekunder berupa data hasil plotting yang diperoleh dari ABD (as built drawing) dari tim konstruksi PAM JAYA dan hasil survei GPS Geodetik. Teknik yang digunakan untuk menganalisis data yaitu membandingkan hasil perhitungan dari metode Euclidean Distance yang menerapkan konsep phytagoras terhadap hasil aktual dari penggunaan GPS Geodetik CHCNAV i50. Hasil perbandingan menunjukkan adanya selisih hasil ploting dari perhitungan pythagoras terhadap hasil survei GPS yang memiliki radius pergeseran kurang dari 20 meter